2022
DOI: 10.2196/36028
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Telerehabilitation in Older Adults With Musculoskeletal Conditions: Systematic Review and Meta-analysis

Abstract: Background Real-time telerehabilitation (TR) is a new strategy for delivering rehabilitation interventions to older adults with musculoskeletal conditions, to provide continuity to conventional services and mitigate travel-related barriers. Objective We aimed to examine the effectiveness of treatment delivered via real-time TR services compared to conventional services among older adults with musculoskeletal conditions, in terms of physical performance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
3
5
0
Order By: Relevance
“… 112 Real-time telerehabilitation was found to improve physical performance at the same level as in-person rehabilitation in older individuals with musculoskeletal conditions. 113 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 112 Real-time telerehabilitation was found to improve physical performance at the same level as in-person rehabilitation in older individuals with musculoskeletal conditions. 113 …”
Section: Resultsmentioning
confidence: 99%
“…It is recommended that PRM physicians prescribe telerehabilitation for patients with health conditions for which there is already some evidence of efficacy or at least clinical positive experiences. These include neurological disorders in general [SoE: I-IV; 38 - 40 SoR: A] specifically including stroke 42 , 43 [SoE: I; 44 - 49 SoR:A], traumatic brain injury [SoE: I 51 (particularly for cognitive rehabilitation); SoR: A], Parkinson’s disease [SoE: I; 52 - 54 SoR: A], multiple Sclerosis 55 - 59 [SoE: I (low level); 55 SoR: A] and spinal cord injury [SoE: II-IV; 60 - 65 SoR: A ] and respiratory conditions 70 [SoE: I; 71 - 76 SoR: A], cardiovascular conditions [SoE: I; 77 - 84 SoR: A], musculoskeletal conditions 73 , 74 such as knee osteoarthritis [SoE: I; 87 - 89 SoR: A] and orthopedic conditions such as joint replacement surgery [SoE: I; 90 - 92 SoR: A], low back pain [SoE: I; 94 SoR: A], fibromyalgia [SoE: II; 95 SoR: A], shoulder pain [SoE: I (very low); 96 SoR: A], COVID-19 including post COVID-19 condition [SoE: I; 99 - 103 SoR:A], low vision [SoE: II (very low); 104 SoR: A] and others such as metabolic syndrome [SoE: IV; 105 SoR: A] burns [SoE: II; 106 SoR: A] and urinary incontinence [SoE: IV; 107 SoR: A] as well as rehabilitation fields such as cancer rehabilitation [SoE: (insufficient); 108 , 109 SoR: A], geriatric rehabilitation in general [SoE: I; 110 - 113 SoR: A] and specifically for those with cognitive impairment [SoE: I; 66 SoR: A] and pediatric rehabilitation [SoE: I; 114 , 115 SoR: A] (may not be limited to those as evidence emerges).…”
Section: Recommendations For Prm Professional Practice In Telerehabil...mentioning
confidence: 99%
“…Health equity considerations highlight the importance of developing interventions that specifically address the barriers and concerns felt by older patients. Evidence suggests that musculoskeletal digital programs are feasible in this population [ 44 - 47 ]. In this study, we observed higher adoption than previously reported for older adults [ 45 , 46 ], as well as a higher likelihood of starting the intervention than their younger counterparts, suggesting that the possible distrust phenomenon was overcome in this particular cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Remote monitoring and guidance through telecommunication technologies have increasingly been recognized as a viable approach to improve individualized care, facilitate timely intervention, empower individuals, and encourage self-management [18,19]. Several techniques have been employed for remote monitoring and guidance in telerehabilitation, including secure messaging and calling, mobile apps, videoconferencing, and healthcare platforms.…”
Section: Remote Monitoring and Guidance Methodsmentioning
confidence: 99%
“…Although two reviews have summarized the beneficial effects of videoconferencing interventions on telerehabilitation in older adults with musculoskeletal conditions [18] and individuals with stroke [19], there is no systematic review of the effects of telerehabilitation with remote monitoring and guidance to improve balance and gait performance in different populations. Indeed, remote monitoring and guidance allow for ongoing assessment, immediate feedback, adjustment of exercise intensity, timely interventions, and improved relationships between users and healthcare professionals, which can enhance the overall efficacy and success of the telerehabilitation program.…”
Section: Introductionmentioning
confidence: 99%